Rancang Bangun Tempat Pembuangan Sampah Otomatis Berbasis Internet Of Things (IoT) - Priansyah, Dwiki; Sutresna, Jaka (CV. Shofanah Media Berkah, 2024)
The rubbish bins in the PORIS GAGA BARU environment are currently not fully utilized due to the lack of innovation in rubbish bins, and also the low level of public awareness in disposing of rubbish properly. On the other hand, the impact of waste processing that is not well integrated, results in many neglected waste bins being found. The condition is worrying, full, crowded so that it really disturbs the comfort of the environment, but it is not immediately cleaned by officers. This is what makes people reluctant and less interested in disposing of waste properly. This research aims to build a monitoring application and automatic system for smart trash based on Internet of Things technology using the C programming language using the Arduino IDE. The choice of the Arduino IDE platform based on the Internet of Things (IOT) for application development apart from being open source and easier to operate, and the flexible nature of Arduino is also one of the reasons and uses C language. Test results for sending sensor data to the web server via the wireless LAN network experienced a delay ranging from 1 to 3 seconds and testing the ultrasonic sensor on the response of the servo motor actuator experienced a delay ranging from 0 to 3 seconds.